2010
DOI: 10.1002/jmv.21939
|View full text |Cite
|
Sign up to set email alerts
|

Chronic liver disease and cirrhosis among patients with hepatitis B virus infection in northern Portugal with reference to the viral genotypes

Abstract: International audienceThe prevalence of infection with hepatitis B virus in Portugal is around 1% of the population; 20-30% of those infected typically develop cirrhosis. The study focuses on the epidemiological profile of patients with hepatitis B infection and liver damage, in particular, cirrhosis. Of the 358 individuals that comprised the study, a liver biopsy was performed in 249 to identify the presence of cirrhosis. Cirrhosis was observed in 59 patients (23.7%) The Child-Pugh classification was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…MSM were infected with genotype A and DU with genotype D, but both groups had an equally high rate of developing chronic infections. Mota et al have shown that this also counts for the chronic sequelae of an HBV infection, such as cirrhosis [18].…”
Section: Discussionmentioning
confidence: 98%
“…MSM were infected with genotype A and DU with genotype D, but both groups had an equally high rate of developing chronic infections. Mota et al have shown that this also counts for the chronic sequelae of an HBV infection, such as cirrhosis [18].…”
Section: Discussionmentioning
confidence: 98%
“…Finally, our data is consistent with a number of previously epidemiological results reported in Germany, confirming the validity of our assessment. 13,23 In conclusion, we found significant rates of advanced and untreated chronic hepatitis B infection in the largest European cohort of treatment-naïve patients. Treatment decisions in our multi-ethnic setting were predominately based on serology including viral DNA PCR results and transaminase levels.…”
Section: Therapy Indicationmentioning
confidence: 58%
“…Using 2017 EASL criteria, we grouped our study sample into three treatment categories (s. 22,23 Nevertheless, our study is unique in that all subjects were treatment naïve and presented for first evaluation of disease activity and liver fibrosis. Our combined findings demonstrate a high burden of preventable morbidity in this population and underscores the need for specialized diagnostics and care.…”
Section: Therapy Indicationmentioning
confidence: 99%
“…It has been reported that infection induces not only innate immune responses but also adaptive immune responses against microorganisms; however in most cases, this fails to eradicate the microorganisms. By contrast, permanent infection ultimately triggers chronic inflammation and further leads to the damage of the body (42,43). It is well accepted that Helicobacter pylori infection triggers production of various cytokines, including IL-1β, IL-6, IL-8, IL-18, IL-32, TNF-α and IL-6, which are known to have important roles in chronic inflammation and ultimate disease outcome (10,14,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%